MOF‐Derived Bifunctional Cu3P Nanoparticles Coated by a N,P‐Codoped Carbon Shell for Hydrogen Evolution and Oxygen Reduction - Wang, Rui; Dong, Xi‐Yan; Du, Jiao; Zhao, Jin‐Yan; Zang, Shuang‐Quan (Advanced materials (Weinheim), 2018)
Metal–organic frameworks (MOFs) have recently emerged as a type of uniformly and periodically atom‐distributed precursor and efficient self‐sacrificial template to fabricate hierarchical porous‐carbon‐related nanostructured functional materials. For the first time, a Cu‐based MOF, i.e., Cu‐NPMOF is used, whose linkers contain nitrogen and phosphorus heteroatoms, as a single precursor and template to prepare novel Cu3P nanoparticles (NPs) coated by a N,P‐codoped carbon shell that is extended to a hierarchical porous carbon matrix with identical uniform N and P doping (termed Cu3P@NPPC) as an electrocatalyst. Cu3P@NPPC demonstrates outstanding activity for both the hydrogen evolution and oxygen reduction reaction, representing the first example of a Cu3P‐based bifunctional catalyst for energy‐conversion reactions. The high performances are ascribed to the high specific surface area, the synergistic effects of the Cu3P NPs with intrinsic activity, the protection of the carbon shell, and the hierarchical porous carbon matrix doped by multiheteroatoms. This strategy of using a diverse MOF as a structural and compositional material to create a new multifunctional composite/hybrid may expand the opportunities to explore highly efficient and robust non‐noble‐metal catalysts for energy‐conversion reactions. Cu3P nanoparticles coated by a N,P‐codoped carbon shell (hierarchical porous carbon matrix) are prepared using a novel Cu‐based metal–organic framework (MOF) containing dual linkers as a template and single precursor. The Cu3P@NPPC catalyst demonstrates a high specific surface area and affords remarkable bifunctional electrocatalytic performance for hydrogen evolution reaction and oxygen reduction reaction with long‐term durability for both reactions.